Bank efficiency in New Zealand: a stochastic frontier approach. Issue 2 (4th May 2019) - Lu, Ying Fang; Gan, Christopher; Hu, Baiding; Toh, Moau Yong; Cohen, David A
ABSTRACT: A parametric stochastic frontier analysis approach is employed to examine the cost and profit efficiency of banks in New Zealand over the study period of 2002–2011. Our result shows that foreign banks exhibit higher average cost and profit efficiency than domestic banks. We further document that Australian-owned banks operate more efficiently than foreign banks from other nations, supporting the limited global advantage hypothesis. Other distinguishing determinants of banks' cost and profit efficiencies are bank size, equity ratio, asset quality, market concentration, interest rate, inflation and unemployment level. Lincoln University (LU).